Cyanide and protein content of Cassava roots and leaves (Manihot esculenta Crantz) from selected sources in Iloilo - Fuentebella, Rose Michelle Chiefe (2007.)
Sources of cassava samples included 14 selected cassava farms within Iloilo and six common market places. Two major varieties of cassava were collected, the white root variety or the Datu I red leafstalk and the yellow variety with yellow green leafstalk of the Lakan I. The cyanide protein of each were determined., The kit developed by sodium picrate method was used in all analysis. The differences of the cyanide and protein levels of cassava roots and of different varieties among different sources are shown in this study. Statistical results showed tha the differences in the concentrations of protein and cyanide in cassava roots and from different sources were significant at 0.05 level. Cyanide concentrations are higher in the than in the roots with spectrophotometric values ranging from 50.49+-1.4 mg/k to 388.08+-11.2 mg/kg for the two varieties. For the roots, recorded results were between 12.87+-4.2 mg/kg to 135.63+-7.0 mg/kg. Storage of cassava roots has an effect on its cyanide content. when storage period lengthen cyanide decreases. The decrease for each day is significant at 0.05 level. Protein contents of cassava roots and are low with a total soluble protein between 0.15 percent to 0.54 percent in the roots and 0.24 percent to 0.59 percent on the. Cassava have higher protein contents than the roots. There is a significant correlation (directly proportional) at 0.05 level between the protein and cyanide contents of the roots and of the cassava. The type of soil based on GPS generated data from Bureau of Soils and Water Management, Department of Agriculture, for each source was also noted and compared with the cyanide content of the cassava roots. Statistical results show that there is no significant difference on the cyanide levels of roots on different soil types.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Cassava (Manihot esculenta Crantz)